Nonlinear viscoelasticity of one dimensional filler reinforced elastomer composites - Jana K.K.; Patel M.; Rana D.; Maiti P. (My University, 2025)
In this chapter, we review the elastomeric composites with different types of one dimensional nanofillers e.g. nanotubes, nanorods and nanofibers. Various elastomers and nanofillers have been considered along with the preparation methods of the composites. The dispersion level and surface morphologies have been reported having various fillers and how do they vary with the chemical modifications on the filler along with the effect of dispersing agent. The improvement in thermal and mechanical properties including dynamic mechanical properties of elastomers has been discussed in presence of one-dimensional nanofillers. Viscoelasticity has been reviewed for elastomeric systems and, especially, how the non-linearity appears in presence of one-dimensional filler. Rheological properties including curing kinetics, storage and loss modulus, and complex viscosities as a function of frequency of the nanocomposites have been discussed in detail. Dynamic mechanical studies related to various elastomer nanocomposites with various one dimensional fillers have been reported with possible explanations. The influence of the nature of fillers with their chemical modifications of one-dimensional filler on the viscoelasticity has also been assessed. © Springer International Publishing Switzerland 2014.